Immoral Offense Eligibility as Criminal Acts Objects for Restorative Justice Filing - Oktobrian, Dwiki; Putro, Guntur Pembayun; Swastiko, Aura Salsabila Ayodya (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Restorative Justice has experienced a new phase in Indonesia since 2020. Since that year, the Police and the Prosecutor’s Office have been competing to formulate internal regulations as a form of deadlock in revising the Indonesian Criminal Code Procedure (KUHAP), one of the new substances of which is the idea of Restorative Justice. Restorative Justice allows a case to not proceed to the court based on a peace agreement between the victim and the offender to create the restoration for the victims and social harmonization. Recently, there have been cases in Indonesia regarding the use of Restorative Justice in immoral cases, such as rape, that is then reconciled by marrying the victim and the offender. Such marriage in no way will bring happiness or restore the victim’s condition but adds to the suffering of the victim and further destroys social harmony. This phenomenon is analysed with a normative approach which shows that the factors for the emergence of daunting peace under the pretext of Restorative Justice arise from the regulations dissimilarity between the Police and the Prosecutor’s Office; only in the Prosecutor’s Office regulation, immoral cases are cases that are excluded as objects of cases in Restorative Justice. Police regulations improvement must be carried out immediately so that the practice of marrying the victims with their offenders in immoral cases can be completely terminated from the start. Even a peace process proposal for immoral crime cases should not need to be facilitated because of the heavy impact felt by the victim or their family.